The equivalence of the equation is 5x + 48 = 5x + 3.
Since 48 cannot be equal to 3, hence there are no solution.
<h3>What is the value of x?</h3>
Given the equation; x-4[ x - 2( x + 6) ] = 5x + 3
We remove the parentheses
x-4[ x - 2( x + 6) ] = 5x + 3
x-4[ x - 2x - 12 ] = 5x + 3
x - 4x + 8x + 48 = 5x + 3
5x + 48 = 5x + 3
We can go further and collect like terms
5x - 5x + 48 = 3
48 ≠ 3
Since 48 cannot be equal to 3, hence there are no solution.
Learn more about equations here: brainly.com/question/14686792
#SPJ1
Answer:
Step-by-step explanation:
(distance) d = (speed) s * t (time)
= 55km/h * 12.30m/s
= 11.275 km
= 11.275 * 1000
= 11275m
Answer:
0.375
Step-by-step explanation:
Answer:
4x+12
Step-by-step explanation:
Answer:
I don’t know
Step-by-step explanation: